2022
DOI: 10.22226/2410-3535-2022-3-177-183
|View full text |Cite
|
Sign up to set email alerts
|

The effect of testing conditions on stress corrosion cracking of biodegradable magnesium alloy ZK60

Abstract: The effect of the chemical composition, temperature, circulation and pH of the simulated body fluid (SBF) on the corrosion and stress corrosion cracking (SCC) susceptibility of the alloy ZK60 was studied through the immersion and slow-strain rate tensile (SSRT) testing respectively. It is found that both the corrosion and SCC susceptibility of the alloy is significantly affected by chemical composition and adjustment of pH level of SBF, while the temperature and circulation of the SBF exert a minor effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This was explained primarily by a more resistant corrosion products layer. Merson et al examined another popular Mg-Zn-Zr alloy, ZK60, in two similar solutions [ 163 ]. It was found that the difference in the corrosion rate between the two solutions was not very large.…”
Section: Corrosion Properties: Modern Insights and Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…This was explained primarily by a more resistant corrosion products layer. Merson et al examined another popular Mg-Zn-Zr alloy, ZK60, in two similar solutions [ 163 ]. It was found that the difference in the corrosion rate between the two solutions was not very large.…”
Section: Corrosion Properties: Modern Insights and Challengesmentioning
confidence: 99%
“…The pH level can be maintained in different ways. The partial replacement of the medium was used in [ 144 , 163 ]: when a certain pH level was reached, the solution was evacuated from the cell, and the fresh solution was supplied. The procedure was fully automated through the use of a digital pH meter, an electronic controller, and a dual-head peristaltic pump.…”
Section: Corrosion Properties: Modern Insights and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it will not be enough to improve the corrosion resistance of magnesium alloys only. [ 11–13 ] It has been stated in the literature that when the stress corrosion crack reaches critical dimensions, the samples may suffer unexpected damage even under a tensile strength of 30%. In several studies in the literature, the effects of different Mg alloys coated with the PEO method on SCC were investigated, and it was stated that the samples coated with the PEO method slightly improved the stress corrosion resistance of the Mg alloys.…”
Section: Introductionmentioning
confidence: 99%